Idiosyncratic Shocks, Lumpy Investment and the Monetary Transmission Mechanism - Michael Reiter; Tommy Sveen; Lutz Weinke (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
Standard (S,s) models of lumpy investment allow us to match many aspects of the micro data, but it is well known that the implied interest rate sensitivity of investment is unrealistically large. The monetary transmission mechanism is therefore a particularly clean experiment to assess the macroeconomic relevance of any investment theory. Our results show that lumpy investment can coexist with a realistic monetary transmission mechanism, but that we are nevertheless still a step away from a micro-founded theory of monetary policy.
Keywords: E22; E31; E32; 330; Lumpy Investment; Sticky Prices